The influence of the clustering and density of establishments along Maginhawa Street on the consumer purchasing decision in terms of choosing an establishment - Pua, Sandra; Rebueno, Neil Jerome; Tomacruz, Mary Delia G. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The agglomeration of food establishments have been drawing numerous people from different cities to dine in the said location. With this sporadic trend, this study aims to determine the relationship of the agglomeration of food establishments, from the intersection of Malingap Street and Maginhawa Street until the intersection of Mahusay Street and Maginhawa Street, and the purchasing decision of consumers in the said area. Respondents were asked to consider what factors attract them to dine in Maginhawa, despite the existence of food cafeterias in nearby schools and fast foods along Philcoa. Furthermore, if discusses the impact of business clustering in a specific area and how word of mouth marketing has helped in boosting people traffic in areas that food establishment cluster.
Thesis (BS Hotel, Restaurant and Institution Management)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines; Restaurants -- Philippines -- Quezon City